Informal Payments in Health Sector and Policies to Deal With (A Review Study) - Abdolvahed Khodamoradi; Arash Rashidian; Siamak Aghlmand; Mohmad Arab (Tehran University of Medical Sciences, 2015)
Background: Informal payments are paid to individuals /health care providing organizations offering as cash or non-cash and are formed out of formal payment channels. This study aim at identifying the types of informal payments, causes, effects and policies to deal with them.  Materials and Methods: This study was a review  one and relative  published articles identified by searching valid database ( Medlib, SID, Pub Med, Science Direct and Google Scholar)using keywords with their equal in Persian (informal payment and unofficial payment) and 128 articles were extracted. The articles refined step by step. In conclusion, 20 articles were selected according to study aims. Results: The study findings consist of five main sections including the definition and form of informal payments, the existent causes of informal payments, effects of informal payments, statistics of informal payments in Iran and the world and policies to dealing with this important issue. Conclusion: Due to the high prevalence of informal payments and severe negative effects on justice and respectable governance, policy-makers should focus on this issue and reduce its effects. Although, strategies to control informal payments are limited but strategies including regulation payment and medical tariffs, regulating power abuse, providing incentives and increasing responsibility of healthcare professionals, and changes in public perception are proposed.